Evaluation of the efficacy of tamsulosin with or without deflazacort for stone clearance after extracorporeal shockwave lithotripsy for upper ureteral and renal calculi - T. P., Rajeev; Gupta, Nitin; Baruah, Somour J.; Barua, Sasanka K. (International Journal of Research in Medical Sciences, 2016)
Background: Medical expulsive therapy in the form of alpha blockers, corticosteroids, calcium channel blockers is being used with success for medical treatment of lower ureteric calculus. Adjunctive use of these therapeutic agents in post extracorporeal shockwave lithotripsy period is also being tried.With this background, we evaluated the efficacy of tamsulosin with or without deflazacort for various outcome factors after ESWL of upper ureteral and renal calculi. Methods: A Prospecive study during period from February 2014 to April 2015 including a total of 90 patients with solitary upper ureteral or renal calculus who underwent ESWL was conducted. Patients were divided into three groups. Group A(30 patients) were given standard therapy (analgesics and antibiotics for 5 days), Group B (30 patients) were given standard plus tamsulosin (0.4 mg once daily) for 4 weeks and Group C (30 patients) were given standard therapy plus tamsulosin (0.4 mg once daily) and deflazacort (6 mg twice daily) for 4 weeks . Patients were evaluated at 2 and 4 weeks post ESWL with X ray KUB and USG. Results: At the end of 4 weeks, 10, 17, and 26 patients in group A, B and C respectively cleared their stones. Out of these 2, 6 and 19 patients in group A, B and C respectively cleared their stones in first 2 weeks. Clearance in group C was significantly higher as compared to group A and B. Conclusions: Addition of alpha-blocker tamsulosin along with deflazacort post ESWL for renal and upper ureteric calculi increases the stone expulsion rate and reduces the expulsion duration as shown by highly statistically significant results in group C.